PENGARUH KEGUNAAN, KUALITAS INFORMASI DAN KUALITAS INTERAKSI LAYANAN WEBSITE PERPUSTAKAAN UNIVERSITAS RIAU TERHADAP KEPUASAN PENGGUNA (Studi pada mahasiswa Universitas Riau dengan menggunakan metode WebQual 4.0) - ", Rosania; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Internet as a new media, nowadays, has function in providing the information without limit. Internet usage in education especially use in the college can support the academicians to gather the information from a website that specially designed by the University. In this research the writer use a quantitative descriptive approach that aims to search the influence of the usability, the information quality and the service interaction quality of Riau University library’s website regarding to the user satisfaction using a questionnaire as a tool in collecting data that the queries formed by instrument of method named WebQual 4.0. Population in this research is all of students of Riau University totally sample to 100 correspondents which are selected by using a combination between cluster sampling and accidental sampling technique. The writer uses a multiple linear regression in analyzing data and a statistical product and service solutions (SPSS) software version 20 for Windows in processing data. The result shows there is a simultaneously positive effect between the usability, the information quality and the service interaction variables to user satisfaction. Parsially, the usability and the information quality variables shows the positive effect but insignificantly against to user satisfaction and the service interaction quality variable of Riau University library’s website shows the positive effect and significantly influence the user. Counting the satisfactory of Riau University students to this research instrument shows that the dominant answer are satisfied, but the time accuracy of updating information and fulfillment for services shows unsatisfied.Keywords: Information Quality, Library’s Website, New Media, Service Interaction Quality, Usability, User Satisfaction, WebQual 4.0